Interrupting the seams: The principle of preventive burn reconstruction. Issue 3 (July 2019) - Papp, Anthony A.; Berhanu, Aaron E.; Thomas, Mark R.; Pham, Tam N.
Highlights: Burn surgery should be planned in a way that reconstruction prevents or minimizes scar contractures. Interrupting linear seams between skin grafts is important. Local transposition and advancement flaps can be used to recruit vascular uninjured tissue to the area of reconstruction. Preventive burn reconstruction is simple and does not really add to operating time.